2018
DOI: 10.1017/s095026881800314x
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of norovirus infection caused by ice cubes and a leaking air ventilation valve

Abstract: A gastrointestinal outbreak was reported among 154 diners who attended a Christmas buffet on the 9 and 10 December 2016. A retrospective cohort study was undertaken. Faecal samples, water, ice and an air ventilation device were tested for indicators and routine pathogens. Altogether 26% (24/91) fulfilled the case definition of having typical viral gastrointestinal symptoms. Norovirus genogroup I was detected in faecal samples from three cases. One of these cases tested positive also for sapovirus and had a fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…To target the actions, similar basic epidemiological actions to human cases need to be taken with animal or food exposures. The data needs to be carefully described in terms of time-place-person (animal/food) (Jalava et al, 2018;Morgan, 2019). To resolve the outbreak, environmental epidemiologists interview the human case patients carefully and possibly other seafood market visitors about their activities in the market and exceptional events they may have observed or taken part in.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…To target the actions, similar basic epidemiological actions to human cases need to be taken with animal or food exposures. The data needs to be carefully described in terms of time-place-person (animal/food) (Jalava et al, 2018;Morgan, 2019). To resolve the outbreak, environmental epidemiologists interview the human case patients carefully and possibly other seafood market visitors about their activities in the market and exceptional events they may have observed or taken part in.…”
Section: Main Textmentioning
confidence: 99%
“…Nice thing about food trace back is that it is almost always possible, yet laborious, to reconstruct afterwards (in comparison to human movements) as money follows the lots of animals, documentation, taxation and selling spots in the market (Keto-Timonen et al, 2019;Self et al, 2019). Finding out the route of transmission is of uttermost importance to implement effective prevention methods (Jalava et al, 2018). Assuming that this outbreak is indeed due to contaminated food, then it represents a clear example as to why food control is important.…”
Section: Main Textmentioning
confidence: 99%
“…Outbreaks of infectious diseases are common, and usually happen through one of several means of transmission: food, water, person-to-person or environmental. Regardless of the initial means of transmission, outbreaks are followed by spreading through direct human contacts ( Jalava, Kauppinen, Al-Hello, & Räsänen, 2019 ). Initial human-to-human transmission was limited, and cases clustered around the Huanan market, mainly among elderly men.…”
Section: Is Covid-19 the First Respiratory Transmitted Outbreak Whichmentioning
confidence: 99%
“…Outbreaks of gastroenteritis due to contaminated ice have been reported in other parts of the world. [1][2][3] For example, a major outbreak of hepatitis A in Lampang and Chiang Rai, Thailand, affecting 906 people, was reportedly due to contaminated ice cubes. 4 Initial investigations pointed to an ice factory in Chiang Rai Province where water is drawn from artesian wells that were contaminated with coliforms.…”
Section: Introductionmentioning
confidence: 99%
“…The outbreak was also reported to be linked with ice cubes from 3 vending machines with high levels of heterotrophic bacteria. 3 Studies from various countries have shown that the microbiological quality of ice manufactured for use in foods and drinks could be a cause for concern. 1,[5][6][7] These studies showed that Escherichia coli, coliforms, and a variety of microorganisms could be present in ice products demonstrating either the poor quality of source water used or a lack of hygiene in the production process or handling or both.…”
Section: Introductionmentioning
confidence: 99%